Effects of storage method on DNA degradation in old bloodstain samples. (December 2015) - Hara, M.; Nakanishi, H.; Takahashi, S.; Tamura, A.; Yoneyama, K.; Saito, K.; Takada, A.
Abstract: The effects of different storage methods on both DNA degradation and the results of preliminary blood tests were evaluated. Bloodstains stored at room temperature, 4 °C, –20 °C, and –80 °C for 20 years; whole blood samples stored at –20 °C and –80 °C for 20 years; and fresh whole blood samples were analyzed. DNA degradation was evaluated by quantifying the ratios of 305 and 129 base pair (bp) fragments to 41 bp fragments. Preliminary testing included leuco-malachite-green staining, anti-human hemoglobin (Hb) testing by immunochromatography, and the detection of the hemoglobin-beta (HBB) mRNA. Bloodstains stored at room temperature and 4 °C were more highly degraded than fresh blood, as indicated by the ratio of 129:41 bp DNA fragments and 305:41 bp DNA fragments. All samples tested positive using leuco-malachite-green staining and anti-human Hb assays. HBB was not detected in any whole blood samples stored at –20 °C or –80 °C, although HBB was detected in all bloodstain samples. Therefore, to prevent DNA degradation during long-term storage, it is recommended that blood samples be stored at below –20 °C. In addition, stored bloodstains are suitable for preliminary tests of blood, rather than storing blood.